Acute effects of strength and endurance exercise on serum BDNF and IGF-1 levels in older men - Arazi, Hamid (BMC Geriatr, 2021)
BACKGROUND: Regarding an important effects of physical exercise on brain function in elders, the aim of this study was to examine the effects of strength and endurance exercise on brain neurobiological factors in older men. METHODS: Thirty older men volunteered to participate in this study and were randomly assigned to strength, endurance and control groups. The subjects in strength group performed two circuits of resistance exercise (6 exercises with 10 repetition of 65–70% of one repetition maximum), while endurance group performed 30 min running with 65–70% of maximal heart rate. Blood was obtained pre and post-exercise to determine changes in serum BDNF, IGF-1 and platelets. RESULTS: After exercise, both the strength and endurance groups showed significant increases in serum BDNF and IGF-1 concentrations and platelets at post-exercise and in comparison to control group (p < 0.05). In addition, no statistically significant differences were detected between the strength and endurance groups at post-exercise. CONCLUSION: Our findings indicate that both the strength and endurance interventions are effective in elevating BDNF, IGF-1, and platelets, without significant differences between them.